Management of Paranoid Schizophrenia with Suicide Risk and Command Hallucinations in a Religious Leader Post-COVID-19 Infection: A Case Report - Gemilang Mutsaqqofa Arsyadana; Era Catur Prasetya (PSPP JOURNALS, 2026)
Paranoid schizophrenia is a severe mental disorder manifested by hallucinations and delusions. This case report presents the comprehensive management of a thirty three year old male religious leader diagnosed with paranoid schizophrenia, who exhibited a high psychiatric emergency risk of suicide attempts driven by command hallucinations. Clinical evaluation revealed that the exacerbation of psychotic symptoms was triggered by the interaction between neurobiological vulnerability post coronavirus infection and chronic psychosocial stress due to severe financial debt. The patient displayed somatic symptoms, panic attacks, and massive suicidal ideation. Combination pharmacotherapy using chlorpromazine and risperidone proved effective in reducing positive symptoms and acute agitation during the stabilization phase. Nevertheless, the prognosis is considered poor due to persistent environmental stressors including family conflicts. A holistic approach involving psychoeducation is absolutely necessary to prevent relapse and mitigate fatal risks in the future.